2014
DOI: 10.1136/bcr-2013-202612
|View full text |Cite
|
Sign up to set email alerts
|

Leucoerythroblastosis and thrombocytopenia as clues to metastatic malignancy

Abstract: SUMMARYThe association of metastatic breast cancer presenting as thrombocytopenia and anaemia is demonstrated in the following case of a 79-year-old woman. Her main symptoms were abdominal pain, altered bowel habit and weight loss. Without a clear causative pathology, she underwent a CT scan which demonstrated multiple sclerotic bone lesions. With a raised CA15-3 and strong oestrogen receptor positivity on immunohistochemistry on a trephine bone marrow biopsy, a diagnosis of metastatic lobular breast cancer wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…Cases of breast cancer related microangiopathic hemolytic anemia (MAHA) has been reported, albeit rarely. [ 12 14 ] In those cases, the anemia and thrombocytopenia raised concern for bone marrow metastasis and indicated poor prognosis, but its pathophysiology remains largely unknown. Someone speculated it as paraneoplastic phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of breast cancer related microangiopathic hemolytic anemia (MAHA) has been reported, albeit rarely. [ 12 14 ] In those cases, the anemia and thrombocytopenia raised concern for bone marrow metastasis and indicated poor prognosis, but its pathophysiology remains largely unknown. Someone speculated it as paraneoplastic phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Typical OBC cases are women who have adenocarcinoma or poorly differentiated carcinoma in the axillary lymph nodes and who have no evident primary breast lesion. Although less common, other metastatic sites have been reported in several case reports [2][3][4][5][6]. Disseminated carcinomatosis of the bone marrow (DCBM) is diffuse infiltration of the bone marrow by malignant cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that bone marrow metastasis from solid tumors is frequently seen in stomach, prostate, and breast cancer [7,8]. Only a few reports of OBC with DCBM are available in the literature [3,5,6], and findings concerning the treatment and clinical course are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Presentations of myelophthisis can include anemia, thrombocytopenia, neutropenia and varying degrees of pancytopenia. Treatment is generally directed against the underlying malignancy with supportive transfusions as needed, but the condition can be refractory to standard treatments such as chemotherapy [3,6]. With the emerging field of immune checkpoint blockade for cancer, little is known about these new agents and their efficacy in treating solid tumors involving the bone marrow or more generally, metastatic lesions present in the bones.…”
Section: Discussionmentioning
confidence: 99%